2009
DOI: 10.1186/1477-7819-7-35
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to assess the feasibility of evaluation of markers of response to chemotherapy at one day & 21 days after first cycle of chemotherapy in carcinoma of breast: a prospective non-randomized observational study

Abstract: Background: Interest in translational studies aimed at investigating biologic markers in predicting response to primary chemotherapy (PCT) in breast cancer has progressively increased. We conducted a pilot study to evaluate feasibility of evaluating biomarkers of response to PCT at one & 21 days after first cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…According to previous studies, the immunohistochemical (IHC) expression pattern and intensity of different biomarkers may be altered after chemotherapy. [11][12][13][14][15][16] On the basis of these findings, breast cancer epithelial markers, such as CK19, might undergo similar changes, and consequently CK19 should not be used as a target to search for metastatic cells; however, whether these changes occur has not been evaluated until the present study.…”
Section: Introductionmentioning
confidence: 97%
“…According to previous studies, the immunohistochemical (IHC) expression pattern and intensity of different biomarkers may be altered after chemotherapy. [11][12][13][14][15][16] On the basis of these findings, breast cancer epithelial markers, such as CK19, might undergo similar changes, and consequently CK19 should not be used as a target to search for metastatic cells; however, whether these changes occur has not been evaluated until the present study.…”
Section: Introductionmentioning
confidence: 97%
“…Unlike ODonovan (2003) study in 103 breast tissue samples, they showed that Caspase-3 precursor and active form were higher in breast cancer than normal tissue (p=0.0188; p=0.0002) [17]. Similarly, Sharma (2009) showed that tumor biology markers (Bcl-2, Apoptotic Index and Caspase-3) changes occurred 24-48 hours after first neoadjuvant chemotherapy cycles. These markers cpuld be as a factors to predict the response of chemotherapy, but to prove them statistically, need research with a larger sample size [18].…”
Section: Discussionmentioning
confidence: 93%
“…The greatest interest in recent years has focused on the biomarker, Ki-67, as an index of proliferative activity. Numerous previous studies have shown that Ki-67 is an independent predictive marker for a local relapse, and for overall and disease-free survival (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). No previous studies, to the best of our knowledge, have shown lateral differences in Ki-67 in BC.…”
Section: Introductionmentioning
confidence: 80%